Analisis Kemampuan Pemecahan Masalah Matematika Ditinjau dari Self Confidence Siswa SMK Dharma Bakti Bitung: Penelitian - Bander, Silvana Enjelina (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research aims to analyze the mathematical problem-solving abilities of students at SMK Dharma Bhakti Bitung in relation to their level of self-confidence. The study employed a qualitative approach involving six participants, consisting of two students each with low, moderate, and high levels of self-confidence. The selection of participants was based on a Self-Confidence Questionnaire with the following score categories: low (x ≤ 65), moderate (65 < x ≤ 75), and high (75 < x ≤ 100). Data were collected through mathematical problem-solving tests and task-based interviews. The results indicate a relationship between students’ self-confidence levels and their mathematical problem-solving abilities. Students with high self-confidence tend to perform better, while those with low self-confidence often face difficulties. Meanwhile, students with moderate self-confidence demonstrate mixed performance—neither particularly weak nor fully optimal. This study highlights that psychological factors, particularly self-confidence, significantly influence students’ academic achievement in mathematics. Therefore, educators should foster students’ self-confidence to improve their problem-solving skills.